Energy in Nigeria and attendant opportunity for industrial development (Cambridge, Mass. : Arthur D. Little Inc., 1963)
This work is directed towards determining the history of Nigerian energy demand and projecting this demand to 1970.
Report prepared for the Ministry of Commerce and Industry, Federal Republic of Nigeria as part of a program of technical assistance sponsored by the United States Agency for International Development, September, 1963.
occ 16/01/2019
Loans
Keywords: Power resources; Industrialization; Nigeria